Picture yourself learning Microsoft office 2010 - Koers, Diane (Boston, MA, 2011)
WELCOME TO THE WORLD of Microsoft Office 2010! This new Picture Yourself Learning guide from Cengage Learning will help you master the many and varied features of one of Microsoft's most popular products-Microsoft Office 2010. Microsoft Office is a powerful and popular suite of programs that will support many aspects of your everyday work style. For exam-ple, information is provided to help you write a let-ter, create a spreadsheet, produce a professional-looking presentation, and manage your schedule and electronic mail. In addition, you'll learn how to create your own professional-appearing newsletters and other publications as well as create your own Web page, using Microsoft Publisher.
Keywords: Business-Computer program; Microsoft office